Qualidade do sono na síndrome de Down - Beatriz Elizabeth Bagatin Veleda Bermudez; Henrique Yonemuto (Residência Pediátrica)
OBJECTIVE: To analyze the sleep quality of patients with Down Syndrome treated at a specialized outpatient clinic. METHODOLOGY: Data collection was based on the Pittsburgh Sleep Quality Index, a specific tool for quickly and effectively analyzing sleep quality in a random sample of 70 patients between July 2022 and February 2023. As the PSQI is not valid for children under 10 years in Brazil, the common variables of the Childrens Sleep Habits Questionnaire (CSHQ) and PSQI-BR were considered in children to allow data analysis. Statistical analysis of the data was carried out using the R Core Team software. RESULTS: The average age of the 70 participants was 14.4 years old, with 50% male and 57.2% had poor sleep quality. The final scores had a mean of 4.92 (0 + 12). The perceived sleep quality was "good" or "very good" in 77.1%, and 42.9% started sleeping within 30 minutes. All had a sleep duration of at least 6 hours, and 91.4% had a sleep efficiency equal to or greater than 85%. 87.2% had some sleep disorder. The use of sleeping pills occurred in 12.9%, and 77.2% had daytime dysfunction. CONCLUSION: The majority (77.1%) judged their sleep quality to be good, but after a more detailed analysis of their sleep, it was observed that it was poor in 57.2%. It reinforces the longitudinal follow-up of this population in integral health for investigation and treatment.